FUNKCJONOWANIE POMOCY SPOŁECZNEJ W POLSKICH MIASTACH - Woźniak, Zbigniew (Wydział Prawa i Administracji UAM, 2008)
The information obtained from the Local Authority System Analysis of the Association of Polish Cities for the period 2000-2006 indicates an increasing number of phenomena which lead to the worsening o f social security o f inhabitants of Polish towns and cities, and a constant growth o f the number of those who depend on social support. At the same time the value of social allowances is diminishing. The results o f the study into the above show that there is no direct chain o f causation between the funds allocated to social security payments in town budgets and the size of social security threats, or between the outlays on social support on the one hand and the social sphere threats and the wealth of a given town on the other. The relationship between the size of budget outlays, the financing of social support and social risk factors has been found to function much more satisfactorily in smaller towns. An analysis of the security allowances structure paid from municipal budgets that were subject of the study shows that apart from being very rigid, that structure has been for years dominated by different forms o f support to the result that it has only very slightly activated the resources o f the social support beneficiaries. Consequently, although many recipients of social allowances receive support, those payments are only stop-gap solutions, incapable of inducing a radical change in the social and economic situation of the beneficiaries. Therefore the risk o f losing social security continues and the system fails to encourage independence and taking one’s life in one’s hands. The fact that there are no ways to change the conditions that generate the reasons why social support might be required, may, in extreme cases, become an „incubator of inaptitude” because those who become beneficiaries of social care institutions return to them with the same or even grater needs or problems, constantly losing the feeling of social security, incapable o f taking care of themselves. This may lead, in turn, to their entering the spiral o f longterm poverty and helplessness (not to mention the quality of social care).
SOCIAL CARE AND SUPPORT SYSTEM IN POLISH TOWNS